2021
DOI: 10.1080/21655979.2021.1916271
|View full text |Cite
|
Sign up to set email alerts
|

Cisatracurium inhibits the growth and induces apoptosis of ovarian cancer cells by promoting lincRNA-p21

Abstract: As a common muscle relaxant, cisatracurium has shown good antitumor effect on some tumors. Recent studies reported that cisatracurium could inhibit the progression of colon cancer by upregulating tumor suppressor gene p53. However, its role in ovarian cancer and its regulatory effect on p53 and p53 downstream targeting gene long intergenic noncoding RNA p21 (lincRNA-p21) is still unknown. Quantitative Real-time Polymerase Chain Reaction (qRT-PCR) was used to assess the expression of p53, lincRNA-p21 and miR-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Then, we further probed whether fluvastatin exerted protective effects on EC progression via knocking down SIRT6 expression. However, the role of PI3K-mTOR pathway in the mechanism of action of fluvastatin related to SIRT6 still requires further study [ 23 , 24 ]. It was obviously found that depletion of SIRT6 triggered more activated cell viability and stimulated the behaviors of EC cells, including proliferation, migration, invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we further probed whether fluvastatin exerted protective effects on EC progression via knocking down SIRT6 expression. However, the role of PI3K-mTOR pathway in the mechanism of action of fluvastatin related to SIRT6 still requires further study [ 23 , 24 ]. It was obviously found that depletion of SIRT6 triggered more activated cell viability and stimulated the behaviors of EC cells, including proliferation, migration, invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular targets and pathways currently under investigation for drug development in ovarian cancers include, cell cycle inhibitors, mTOR inhibitors, and PI3K inhibitors. A recent study found that cisatracurium can inhibit the progression of OC cells by upregulating lncRNA-p21 activated by p53 inhibiting miR-181b expression, indicating that drugs targeting ceRNA networks are indeed promising in treating OC [ 34 ]. In our study, we found five small-molecule drugs with potential therapeutic efficacy based on OC RNA-seq using bioinformatics analysis, thus guiding the direction for future drug exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability of treated HrGECs was determined with a CCK-8 assay. To determine the cell viability, HrGECs were mixed with 10 µL CCK-8 solution and incubated at 37°C for 2 hours, followed by measuring the absorbance at 450 nm using a microplate reader (J&H technology Co., Ltd, Jiangsu, China) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%